(untitled) (Iraqi Journal of Civil Engineering, 2017)
Most of Iraqi Cities suffering from delaying of the update of Master plan, especially in the period between 1980 and 2003 the main reasons this delay are the Gulf War and the Economic Blockade. Increasing of population is the major factor causes changing in urban land use due to the human demand. These changes cause differences between master plan and real situation. To mention the spatial irregularities in Falujah City, the comparison between the master plan layers and updating land use map layers has achieved in this paper to determine the spatial change and irregularities in the city, that represent the reality of situation in case study . The changes were remarked; the areas of changes were calculated in table and thematic map were produced in our paper to illustrate the goal. This data processed using combination of GIS technique, and global positioning system GPS and geo media software.